Assessment of cumulative health risk in the World Trade Center general responder cohort. Issue 1 (17th November 2017) - Bello, Ghalib A.; Teitelbaum, Susan L.; Lucchini, Roberto G.; Dasaro, Christopher R.; Shapiro, Moshe; Kaplan, Julia R.; Crane, Michael A.; Harrison, Denise J.; Luft, Benjamin J.; Moline, Jacqueline M.; Udasin, Iris G.; Todd, Andrew C.
Abstract : Background: Multiple comorbidities have been reported among rescue/recovery workers responding to the 9/11/2001 WTC disaster. In this study, we developed an index that quantifies the cumulative physiological burden of comorbidities and predicts life expectancy in this cohort. Methods: A machine learning approach (gradient boosting) was used to model the relationship between mortality and several clinical parameters (laboratory test results, blood pressure, pulmonary function measures). This model was used to construct a risk index, which was validated by assessing its association with a number of health outcomes within the WTC general responder cohort. Results: The risk index showed significant associations with mortality, self‐assessed physical health, and onset of multiple chronic conditions, particularly COPD, hypertension, asthma, and sleep apnea. Conclusion: As an aggregate of several clinical parameters, this index serves as a cumulative measure of physiological dysregulation and could be utilized as a prognostic indicator of life expectancy and morbidity risk.